The Psychotherapist’s Personality: Myths and Realities - Popa, Ecaterina; Popa, Brigitte (New Trends in Psychology, 2026)
The personality of the psychotherapist represents a key factor in shaping the quality of the therapeutic relationship and the effectiveness of clinical interventions. Contrary to persistent myths portraying therapists as perfectly balanced, constantly calm, or emotionally detached, empirical evidence indicates that clinical efficacy is more strongly associated with self-awareness, emotional maturity, flexibility, and the capacity to establish authentic therapeutic relationships. Contemporary research on common factors, personality frameworks (including the Big Five, hypostatic, and experiential models), and therapist characteristics suggests that individual diversity in personal style, emotional self-regulation, and adaptability is more predictive of positive therapeutic outcomes than adherence to an idealized personality profile. This article offers a critical analysis of prevailing myths and evidence-based perspectives on therapist personality, integrating theoretical models with empirical findings from the literature. It further explores implications for professional training and development, emphasizing the role of ongoing self-reflection, supervised practice, and personal growth. By aligning personal competencies with professional skills, psychotherapists may enhance therapeutic effectiveness while ethically supporting client transformation. Overall, the findings support a conceptualization of personality as a dynamic and multifaceted construct that continuously interacts with professional roles and relational contexts, rather than as a fixed constellation of traits.